Towards Effective and Fair Fisheries Law Enforcement: Efforts To Strengthen The Principle of Legal Certainty - Waluyo, Joko (The Islamic Education and Multiculturalism Foundation, 2024)
This research discusses the authority to adjudicate fisheries criminal cases in the Republic of Indonesia State Fisheries Management area (WPPNRI) and the regulatory concept based on the principle of legal certainty. This research aims to analyze and discover the nature of the authority and regulatory concept for adjudicating fisheries criminal cases in Indonesia based on the principle of legal certainty. The method used in this research is a normative legal method using data collection techniques through literature study which are then analyzed through step-by-step descriptions of legal interpretation, systematization, evaluation, and legal argumentation. The research results show that the authority to adjudicate fisheries criminal cases at WPPNRI is absolute (absolute competence or attribution) to accept and decide fisheries disputes, and has relative authority (distribution or relative) based on the general court area. This regulatory concept is proposed by reconstructing Article 106 of the Fisheries Law so that the fisheries court becomes the only institution adjudicating fisheries cases. Establishing a fisheries court in each province is expected to end the dualism of authority and create legal certainty. Therefore, it's necessary to reconstruct Article 106 of the Fisheries Law by increasing the number of special fisheries courts, practitioners, and law enforcers to increase synergy between investigators and fisheries supervisors to protect fish resources and ensure their benefits for the welfare of the Indonesian people.